Multicultural Education Paradigm Based Islamic Religious Education in Indonesia - Abdul Muqtadir. S; St.Warda Hanafie Das (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2025)
Multicultural education in Indonesia is a response to the diversity of cultures, ethnicities, religions, and languages that exist in this country. This article discusses the paradigm of multicultural education based on Islamic Religious Education (PAI) as an approach to creating social harmony and increasing tolerance in a plural society. This approach integrates Islamic values with the principles of multiculturalism to create an educational environment that is inclusive, fair and respectful of differences. Thus, education can serve as a guideline for implementing the educational process in order to progress and become better.